Visualisasi Perjuangan Pengerajin Eceng Gondok Di Desa Tuntang Melalui Fotografi Esai Human Interest - Darmawan, Philipus Adi; Adiwibawa, Bernardus Andang Prasetya (Universitas Dian Nuswantoro, 2025)
The mass media exposure or coverage of the Cikidul Community, a business community of water hyacinth artisans in Tuntang Village, is meager, which makes the Cikidul Community less known by the general public, especially its target market. Therefore, Cikidul Community needs to increase its mass media exposure through a photography essay design that visualizes the struggle of water hyacinth artisans. This design uses qualitative research methods through literature studies, interviews, and observations. Data analysis uses a descriptive method with the 5W-1H framework and Jaymi Heimbuch's essay photography design method. This photography essay is displayed through exhibitions, exhibition catalogs, photography books, and social media content with the target of Semarang Regency, Central Java in particular, and the wider community in general.